A genome-wide analysis of courting and mating responses in Drosophila melanogaster females. - Lawniczak, M.K.; Begun, D.J. (Genome, 2004)
In Drosophila melanogaster, seminal fluid proteins influence several components of female physiology and behavior, including re-mating rates, ovulation and oviposition, and sperm use. It is well-known that female flies are not simply passive vessels and that female-mediated interactions with male products are important to female (and thus male) reproductive success. While the population genetics, molecular evolution and physiological effects of seminal fluid proteins have been examined, the genetics and evolution of the female side of these post-mating interactions is unexplored in spite of work showing that female genotype and female-by-male genotype interactions are important determinants of sperm competition outcomes. Here we use microarrays to identify candidate genes involved in the female side of post-mating sexual interactions. We report the results of a whole-genome oligonucleotide chip experiment that reveals 23 genes differentially expressed between virgin females exposed and unexposed to courting males, and 38 genes differentially expressed between virgin and recently mated females. Immune related genes are overrepresented among the mating-influenced candidates. We use quantitative reverse-transcriptase PCR to independently assess gene expression changes for roughly half of the mating-affected candidate genes.